Materiality and metaphor: environment and place in contemporary poetry - Chamberlain, Louise (2015)
This thesis considers literary and critical reverberations of environment and place in order to reframe conceptions of what nature might mean for contemporary poetry. It attends to the timeframe of 1990 – present, assessing how developments in socio-political context and critical thought correspond or conflict with poetic responses. The interdisciplinary reach of the thesis brings together literary geography and ecocriticism, both of which established their roots during this period, putting conventional understandings of place and environment under pressure. The approach encourages a geographical attention to socio-cultural concerns whilst maintaining critical awareness of recent ecocritical focus on materiality, emphasising the potentially productive friction between cultural representation and physical reality. The thesis responds to earlier Romantic paradigms, granting marginalised contemporary poetry a stronger critical agency whilst still accepting the transformations and metamorphoses of literary convention.